Hypothyroidism following sistrunk procedure: Thyroglossal duct cyst or ectopic thyroid? - Hassan Abdullahi Elechi (Wolters Kluwer Medknow Publications, 2021)
Thyroglossal duct cyst is the most common cause of anterior midline neck swelling in children, but ectopic thyroid is an important but rare differential diagnosis. Establishing the orthotopic thyroid gland status is crucial as inadvertent removal of a lone functioning ectopic thyroid tissue in young children could lead to fluttering of growth and development if not identified early. We report the case of a 2 years 10-month-old boy who had Sistrunk's procedure for 'thyroglossal duct cyst': Diagnosed using USS, defaulted follow-up and presented subsequently with growth retardation from hypothyroidism.